THE EVALUATION OF WORKING CAPITAL IN AIRLINE COMPANIES WHICH PROCEED IN BIST - Kendirli, Selcuk; Kaya, Aslihan (Journal of Economic Development, Environment and People, 2016)
The working capital like cash and liquid assets runs the facilities and supports daily activities of firms. This kind of capital is essential to continuity of activities, increase of volume, maintain credibility, reduce impacts of risks and to overcome with extraordinary situation. The working capital management is very important for making profits from activities, especially for dynamic sectors like aviation. The aviation industry which airline companies operate is a very dynamic sector. In this sector working capital has to be managed very professionally and carefully by airline companies. This study aims to assess the airline companies’ working capital in terms of effectiveness. Airline companies which shares traded on BIST will be sample of this study.